Consenso de expertos para el tratamiento antimicrobiano de las infecciones causadas por bacilos gram negativos multirresistentes en pacientes adultos - Carlos Arturo Álvarez-Moreno (Asociación Colombiana de Infectología, 2023)
Bacterial resistance is a high-impact phenomenon for global public health. Although surveillance networks have been built and new technologies have been de-veloped for the resistance phenomenon characterization, there are still several challenges to be addressed. The indiscriminate and uninformed use of antibiotics contributes substantially to the phenomenon of resistance. For this reason, it is essential to develop strategies that increase health professionals' knowledge of prescribing antibiotics according to different factors, including local epidemiology, the infection location, clinical conditions of the patients and better available evidence. This document aims to present recommendations for treating infections caused by multi-drug resistant Gram-negative microorganisms in the hospital context of Colombia. A guideline with 26 evidence-based recommendations is given; the methodology developed was based on a literature search, evidence evaluation, synthesis of information, and expert consensus to assign a level of recommendation.